Negotiating cultural and contextual experiences: Exploring acculturative stress and coping strategies among international students in Canada - Torres-Arends, Irene; Jacobsen, Michele; Lang, Brian; Sharma, Abhijay (Journal of International Students, 2025)
This study identifies the intercultural and contextual stressors experienced by undergraduate international students in a business program at a private Canadian university. Using a sequential mixed-methods design, we drew on Redfield et al.’s (1936) concept of acculturation and Berry’s (2001) theoretical model. First, we invited all international students in the program to complete a survey that included Sandhu and Asrabadi’s (1994) Acculturative Stress Scale. Second, the survey data were complemented by focus groups organized by students’ year in the program. The participants were presented with aggregated survey data to prompt discussion about the results. Intercultural stressors, such as cultural shock and homesickness, pose challenges in adapting to new cultural norms. Contextual stressors, including students’ unmet expectations and uncertainties related to immigration policies, underscore structural issues that intensify students’ challenges.